1996
DOI: 10.2188/jea.6.3sup_49
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Disease A Brief Review of Epidemiological Studies on Ischemic Heart Disease in Japan

Abstract: The age-adjusted death rate from ischemic heart disease in Japan is the lowest among developed countries and the rates have decreased since 1970. The incidences of myocardial infarction in selected populations ranged between 0.12 and 2.56 per 1,000 for middle-aged males, and between 0.00 and 1.52 per 1,000 for females. The incidences of sudden death within 24 hours were from 0.00 to 1.58 per 1,000 for males and from 0.00 to 0.76 per/1,000 for females. The incidences in Japanese populations appeared to be far b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 12 publications
1
16
0
Order By: Relevance
“…There are several reports showing that obesity is a CAD risk factor in Japan, 6,7,[13][14][15][16]20 as it is in Western countries; [1][2][3][4][5][6] however, there are some that show obesity is not a risk factor among the Japanese population. 21,22 The failure of obesity as a CAD risk factor in those studies may be partly explained by the low prevalence of obesity among Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports showing that obesity is a CAD risk factor in Japan, 6,7,[13][14][15][16]20 as it is in Western countries; [1][2][3][4][5][6] however, there are some that show obesity is not a risk factor among the Japanese population. 21,22 The failure of obesity as a CAD risk factor in those studies may be partly explained by the low prevalence of obesity among Japanese.…”
Section: Discussionmentioning
confidence: 99%
“…10 Coronary artery disease was not related in our study probably because of the much lower prevalence of coronary artery disease in Japan. 22 The results of these studies suggest that the presence of other risk factors in hypertensive patients is not an important factor in whether physicians increase medication for treated patients. Our study showed that younger physicians were more likely to increase medication.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, several epidemiological studies failed to show a positive relationship between serum TC and CHD incidence 29,30) . A 15.5-year rural community-based cohort study in Niigata, which was conducted in 1977, has shown no relationship between serum TC and the occurrence of myocardial infarction 29) .…”
Section: Hypercholesterolemia and Chdmentioning
confidence: 99%
“…A 15.5-year rural community-based cohort study in Niigata, which was conducted in 1977, has shown no relationship between serum TC and the occurrence of myocardial infarction 29) . There is a variation in the serum TC levels between rural and urban areas, and CHD mortality may be higher in the urban population than in the rural population 30,31) .…”
Section: Hypercholesterolemia and Chdmentioning
confidence: 99%